Ethnopedagogical Content in the Traditional Art of Sasak Ethnic Group: Gendang Beleq - Alditia, Lalu Muhammad; Nurmawanti, Iva (DIDAKTIKA, 2023)
The integration of culture in education, known as ethnopedagogy, enhances learning effectiveness. However, limited research exists on this topic.Â  Therefore, this study aims to explore ethnopedagogical content in gendang beleq art, serving as a reference for integrating culture and local wisdom in Indonesia. This research adopts a qualitative approach, utilizing a literature study method to gather information from various relevant sources like articles, proceedings, and books. The data was analyzed using a qualitative content analysis approach with thematic analysis. Findings reveal that gendang beleq art contains various ethnopedagogical contents. These include ethnomathematics concepts like geometric shapes (such as half a needle, beam, and tube) and flat shapes (triangles, pentagons, and circles). Additionally, the art form incorporates ethnoscience concepts related to sound, as well as concepts of motion, locomotors in floor formations or patterns, and dance during drum beleq performances. Lastly, it encompasses the content of the Pancasila concept, emphasizing integration, unity, justice, and equality. These findings highlight gendang beleq art as a valuable reference for cultural products and local wisdom, with the potential to enhance ethnopedagogical-based learning implementation.Keywords: Ethnopedagogy, Gendang beleq, SasakÂ ethnic, Traditional art